POTRET PRAKTIK AKUNTANSI ASET BIOLOGIS BERDASARKAN PSAK 241 PADA UMKM PETANI BIBIT - Mawadatullaela; Rini Ridhawati; Wahidatul Husnaini (Jurnal Akuntansi AKTIVA, 2025)
This study aims to analyze the application of biological asset accounting in micro, small, and medium enterprises (MSMEs) of seedling farmers based on PSAK 241. This study was conducted in Batu Kumbung Village, West Lombok, using qualitative methods. The data collection technique used was in-depth interviews with farmers and MSME owners. The data were analyzed using the Miles and Huberman model. The results of the study found that in terms of the recognition and measurement of biological assets, they were essentially carried out in accordance with PSAK 241 because farmers had control over the plants and their potential economic benefits, and used fair value to measure the value of their biological assets. In terms of disclosure and presentation of biological assets, farmers have not prepared formal financial statements that explicitly disclose their biological assets, either in terms of quantity, value, or information about the measurement methods used. As a result, biological assets such as plant seeds are not reflected in the statement of financial position, either as current or non-current assets, and are not classified based on age or growth stage.